Can unconditional cash transfers mitigate the impact of armed conflict on child nutrition in Yemen? - Ecker, Olivier; Maystadt, Jean-Francois (Economic Research Forum, 2021)
The “ignored” civil war in Yemen has caused the world’s worst humanitarian crisis in recent history. Little is known about how to mitigate the detrimental consequences of such protracted violence. We use quarterly panel data to estimate the impact of armed conflict on child nutrition in Yemen and the role of unconditional cash transfers in mitigating the adverse nutritional impact. Our results show that a one-standard-deviation increase in armed conflict intensity reduces the weight-for-height z-scores (WHZ) and mid-upper arm circumference z-scores (MUACZ) of children by 9.6% and 4.4%, respectively, on average. We also find that the studied cash transfer program reduces the nutritional impact by 35.8% for WHZ and 20.4% for MUACZ. Our analysis suggests that if relative stability is restored, unconditional cash transfer programs can be an effective tool to curb rising acute child malnutrition in situations of complex emergencies.